Desenvolvimento de aplicativo para pessoas com deficiência a pontos de lazer, cultura e esporte da cidade de Uberlândia, MG - Borges, Josana Carla Lima (2016)
One scenario presented to society currently deals with the wide participation of citizens, however, one of the most challenging issues is the social inequity. The accessibility of persons with disabilities or reduced mobility to leisure, culture and sport is small, due to the lack of environmental preparation to receive them, as well as the transportation modes. One way to facilitate the movement of those who need accessibility is the use of new technologies. The increasing advancement in informatics brought the development of geotechnologies that uses mathematical and computational techniques for handling and systematization of geographic information that may be in conjunction with mobile technology. This study aimed the development and implementation of an applicative for mobile phones, for the management and provision of information about the accessibility to locations of leisure, culture and sport of the city of Uberlândia, MG. Technical visits were conducted at the sites by the researcher in order to identify: (1) the existence of preferred parking spaces and equipment to external access of the municipal sites for leisure, culture and sport; (2) to verify the existence of adapted urban transportation routes that pass near to the points analyzed; and (3) the existence of accessible routes and adapted points at the bus stops. In order to get the coordinates and consequent geographical location of those points, it was used the Google MapsAPI library and presented thematic maps on the Android platform, which classify the sites as: accessible, partially accessible or inaccessible. The end of the process produced an application for the Android platform named Udiacess, containing a thematic map of Uberlândia with all the information about the accessibility of each site analyzed.